Stability and in vitro digestion study of curcumin-encapsulated in different milled cellulose particle stabilized Pickering emulsions. Issue 1 (20th December 2019) - Lu, Xuanxuan; Huang, Qingrong
Abstract : Figure in vitro lipolysis of curcumin encapsulated Pickering emulsions stabilized by milled cellulose. Abstract : The stability, in vitro digestion profile and phase behavior of Pickering emulsions stabilized by milled cellulose were evaluated to investigate their feasibility as food-grade formulations for encapsulation and delivery of lipophilic bioactive compounds. Curcumin encapsulated in Pickering emulsions exhibited good stability with less than 50% degraded after 30 days' storage. The digestion profiles of emulsions were markedly influenced by lipid type used and digestion buffer employed in simulated small intestinal experiments. The rate and extent of lipolysis of emulsions with medium chain triglycerides were greater than emulsions with long chain triglycerides (soy bean oil and canola oil), reaching complete hydrolysis under both fed and fasted conditions. For comparison, the digestion behaviors of curcumin encapsulated in conventional emulsions were also evaluated. Although the initial digestion rate of Pickering emulsions with long chain triglycerides was slower than the corresponding conventional emulsions stabilized by Tween/Span 80, their total extent of lipolysis was higher than that of conventional emulsions. The bioaccessibility of curcumin encapsulated in Pickering emulsions was higher than in corresponding small molecular weight surfactant stabilized conventional emulsions.